Reviewing role of Corporate governance regarding transactions with related parties and company performance among companies admitted into Tehran Stock Exchange - Matinfard, Mehran; Hassani, Mohammad; Elyasi, Hossein (Ciência e Natura, 2015)
This research reviews the role of corporate governance regarding transactions with related parties and company performance. 85 companies admitted into the TSE were studies during a six months period between 2008 and 2013. Transaction with related parties is a usual trait of commercial activities. For example, some businesses conduct their activities via subsidiary businesses, particular partnerships and related businesses. Transactions with related parties can affect financial situation, financial performance and flexibility of the business. In this research the ratio of non-executive members of the board of directors to total members, membership or non membership of the managing director in the board, size of board and shares of institutional owners have been used as corporate governance variables. Finally, Eviews and Excel software and multi variable regression were used to test the research hypothesis. Results indicate a significant correlation between transactions with related parties and returns on assets. Results also showed that by importing corporate governance variables into the model, explanatory power of model increases and negative effect of transactions with related parties on performance reduces.